2011
DOI: 10.1037/a0021860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic essentialism: On the deceptive determinism of DNA.

Abstract: This paper introduces the notion of genetic essentialist biases: cognitive biases associated with essentialist thinking that are elicited when people encounter arguments that genes are relevant for a behavior, condition, or social group. Learning about genetic attributions for various human conditions leads to a particular set of thoughts regarding those conditions: they are more likely to be perceived as a) immutable and determined, b) having a specific etiology, c) homogeneous and discrete, and, d) natural, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
572
4
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 589 publications
(621 citation statements)
references
References 169 publications
17
572
4
7
Order By: Relevance
“…38 The modification of perceived behavioral control is therefore a concern that should be addressed when genetic susceptibility information is disseminated to individual consumers, emphasizing the nondeterministic, interactive relationship between genes and environment, for example. 9,39 As compared with individuals who learned that they do not have an allele associated with alcoholism, people who learned that they purportedly have such an allele were more likely to actually enroll in a drinking intervention. A less stringent test (i.e., no measure of actual behaviors) indicated that women (but not men) with the purported allele were also more willing to participate in such a workshop as compared with women purportedly without the allele.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…38 The modification of perceived behavioral control is therefore a concern that should be addressed when genetic susceptibility information is disseminated to individual consumers, emphasizing the nondeterministic, interactive relationship between genes and environment, for example. 9,39 As compared with individuals who learned that they do not have an allele associated with alcoholism, people who learned that they purportedly have such an allele were more likely to actually enroll in a drinking intervention. A less stringent test (i.e., no measure of actual behaviors) indicated that women (but not men) with the purported allele were also more willing to participate in such a workshop as compared with women purportedly without the allele.…”
Section: Discussionmentioning
confidence: 99%
“…40 Others have pointed out that the increased fatalism that often accompanies genetic attributions may reduce vigilant behaviors as the genetic influence is interpreted as destiny. 9 Research aimed at reconciling these inconsistencies is needed, as is further theoretical development to examine the moderators involved in behavioral changes following indication of genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations